SIMULTANEOUS ESTIMATION OF LAMIVUDINE AND STAVUDINE IN TABLET DOSAGE FORM BY RP-HPLC: Pharmaceutical Science-Pharmacology - ANBU, JAYARAMAN; C. ROOSEWELT; ANJANA, ASHWINI; RAO, G. SRINIVASA; R. SATHISH (International Journal of Life Science and Pharma Research, 2012)
Lamivudine is a potent ‛‛reverse transcriptase inhibitor ’’ belonging to the class of nucleoside analog reverse transcriptase inhibitor (NARTI). Stavudine is an anti-HIV treatment drug in the class of drugs called nucleoside reverse transcriptase inhibitors (NRTIs). Both are excellent anti-retroviral drugs, widely used clinically in the treatment of infections which are related to immuno deficiency virus. The present combination of Lamivudine and Stavudine was marketed as one tablet dosage form formulation with a dose of Lamivudine 150mg/tab and Stavudine 40mg/tab. Although various methods have been developed for the estimation of Lamivudine and Stavudine individually and in combination with other drugs, no official method has been published with the combination of these drugs. The fixed dose combination of Lamivudine and Stavudine was subjected to simultaneous estimation by Reverse phase HPLC method